Authoritarianism, psychopathy, and resistance to wearing masks during the COVID-19 pandemic: A partial replication and extension of key findings - Prichard, Eric Charles; Turner, K. Amber (Frontiers in Psychology, 2023)
Controversial recent research suggests Americans with more authoritarian tendencies showed less concern about COVID-19 and self-report less mask wearing. The present study set out to replicate this result with a larger sample. The study also sought to extend the original research by investigating how the dark triad traits of narcissism, psychopathy, and Machiavellianism are related to COVID-19 attitudes and behaviors. Nine-hundred ninety-six U.S. high school graduates were asked 8 questions about their level of concern about the effects of the virus on health and finances, how frequently they wore masks, which authority figures they trusted, and whether China was responsible for the virus. Correlational and regression analyses showed that authoritarianism, Machiavellianism, narcissism, and psychopathy were all negatively related to self-reported mask wearing. An explanation is offered for an apparent contradiction between the presented results and studies that showed authoritarian support for lockdowns early during the outbreak.